IMPLEMENTATION OF AUTOMATIC DOOR SYSTEM BASED ON BODY TEMPERATURE USING Arduino UNO AND NODEMCU V3 - Muhammad Afdhol Rizaldi (Journal of Information Technology and Its Utilization, 2021)
So far, the spread of the corona virus disease is very difficult to prevent and reduce because transmission can occur through non-physical contact which can be easily done without being noticed by people when touching common items or objects that are often used, one of which is doorknobs. The design of the automatic door system on the sliding door was made based on body temperature. The purpose of this study is to reduce the occurrence of corona virus transmission through non-physical contact with objects that are often used in this case doorknobs. The infrared temperature sensor is used to measure the temperature when the user wants to enter the room. If the results of the body temperature measurement are normal (below 38ºC), the door will open and then close automatically.